Limited Contribution of Glacier Mass Loss to the Recent Increase in Tibetan Plateau Lake Volume - Brun, Fanny; Treichler, Désirée; Shean, David; Immerzeel, Walter W. (Frontiers in Earth Science, 2020)
The Tibetan Plateau (TP) plays an essential role in the water supply to Asia’s large river systems and, as the largest and highest mountain plateau in the world, it drives the Asian monsoon and influences global atmospheric circulation patterns. The increase in TP lake volume since the mid-1990s is well documented, however the drivers of lake growth remain largely unexplained. In this study we investigate changes in lake and glacier volumes, together with changes in precipitation and evapotranspiration at basin scale. We calculate the contribution of glacier mass loss to the lake volume increase for the period 1994-2015. We demonstrate that glacier mass loss does have a limited contribution to the lake volume increase (19 ± 21 % for the whole TP). Glacier mass loss is thus insufficient to explain all of the lake volume gain, and despite large spread in various products that estimate precipitation and evaporation, we suggest that an increase in precipitation excess (precipitation - evapotranspiration) may be sufficient to explain the lake volume gain.